Comparison of Labrum Resistance Force while Pull-Probing In Vivo and Cadaveric Hips - Takehito Hananouchi; Soshi Uchida; Yusuke Hashimoto; Funakoshi Noboru; Stephen K. Aoki (Biomimetics, 2021)
Cadaver tissue has been identified as the highest-fidelity anatomical representation in terms of the training for orthopedic surgery, including for arthroscopy of a damaged hip labrum. However, hip labrum stiffness in vivo and in cadavers has not been directly compared. The purpose of this study was to compare in vivo and cadaveric hip labrum stiffness during pull-probing with a force sensor. We measured the resistance force of the hip labrum in ten patients during hip arthroscopy (i.e., in vivo) and compared it with ten cadavers, both intact and detached from the acetabulum, using a surgical knife. We confirmed a partial labral tear (i.e., not detached fully from the rim) at an antero-superior potion in all of the patients. The mean highest resistance levels for the hip labrum in the patients (4.7 N) were significantly lower than the intact cadaveric labrum (8.3 N), and slightly higher than the detached labrum (4.2 N). In this study, the stiffness of the cadaveric labrum tissue was similar to that of the in-vivo hip labrum.